FEATURES OF THE SOMATIC STATUS OF EX-SERVICEMEN SUFFERING FROM ALCOHOL ADDICTION - Gaydabrus, A.V.; Linskiy, I.V. (World of Medicine and Biology, 2013)
The paper presents the results of a survey of ex-servicemen who had been treated for alcohol dependence. The patients of the study group was more pronounced involvement of the peripheral nervous system, marked reduction of hemoglobin and AST levels in the serum, indicating a possible heart and kidney damage. By comparing the results obtained that the patients of the study group, signs of chronic intoxication of the heart, whereas among civilian patients had liver disease. Revealed significant differences should be taken into account in the treatment and rehabilitation in these patients.